Yarsan religion and holiness Tanbur - Jazny Muhamad, Zrian (Zanco Journal of Human Sciences, 2023)
Yarsan is an ancient Kurdish independent religion, and it has grown and developed on the foundations and roots of the ancient religions in Kurdistan. The Yarsan Bible is considered as a (Saranjam) of it. It was written in the Goran dialect. kurdish, And it has its own ways. Music is an important section and a main and sacred pillar in the Yarsan religion, and the tambour instrument has become a beacon for it and they play it during the performance of sacred religious ceremonies for them. The tunbur instrument in the Yarsan religion has a prestigious and sacred position, and the finest instruments are played in it when performing their ceremonies. With the development and growth of the Yarsan religion, the mixing of the tunbur instrument increased with ceremonies and worship generation after generation, and its uses spread among many believers in this religion.